2016
DOI: 10.12965/jer.1632552.276
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, cardiorespiratory, and neuromuscular fitness performance in children with cerebral palsy: A comparison with healthy youth

Abstract: The aim of this study was to assess metabolic, cardiorespiratory, and neuromuscular fitness parameters in children with spastic cerebral palsy (CP) and to compare these findings with typically developing children. 40 children with CP (21 males, 19 females; mean age, 11.0±3.3 yr; range, 6.5–17.1 yr; Gross Motor Function Classification System levels 1 or 2) and 40 healthy, age- and sex-matched children completed a test battery that consisted of 8 tests and 28 measures that assessed cardio-respiratory fitness, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…and obesity-related health complications.) 34 Evidence suggests that children with CP have poor cardiorespiratory fitness 35 and excess body 4 and abdominal 3 fat compared to children without CP. Excess body fat in childhood is a strong predictor of cardiometabolic morbidity and mortality in adulthood, 36,37 and elevated abdominal fat may have a unique and profound influence on cardiometabolic disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…and obesity-related health complications.) 34 Evidence suggests that children with CP have poor cardiorespiratory fitness 35 and excess body 4 and abdominal 3 fat compared to children without CP. Excess body fat in childhood is a strong predictor of cardiometabolic morbidity and mortality in adulthood, 36,37 and elevated abdominal fat may have a unique and profound influence on cardiometabolic disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…While the cause and etiology of NDDs vary, the greater likelihood of having complex and unmet healthcare needs, as well as the lack of clinical knowledge about their healthful aging process, are commonalities linking all types of individuals with NDDs. Children with NDDs have low fitness levels, 5,6 excess body fat, [7][8][9][10] poor psychosocial development, 4 and orthopedic issues. 7,11,12 Having complex healthcare needs throughout growth and development could have long-term and lasting implications on adult health status.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of post‐NTFx disease sequela may affect adults with CP more so than the general population because of their overall poorer health status. Studies have shown that children with CP have poor fitness levels, 37 low physical activity, 4 and excess regional 4,38 and total body 39 fat compared to typically developing children and that adults with CP have increased risk for early development of several high burden chronic diseases and multimorbidity, including cardiovascular disease, 9,17 kidney, and liver disease, and mental health disorders 17 . It is possible that the greater lifetime burden of unhealthful aging predisposes adults with CP to adverse postfracture complications, including RD.…”
Section: Discussionmentioning
confidence: 99%